PCSK9 Activity Is Potentiated Through HDL Binding. Issue 11 (12th November 2021) - Burnap, Sean A.; Sattler, Katherine; Pechlaner, Raimund; Duregotti, Elisa; Lu, Ruifang; Theofilatos, Konstantinos; Takov, Kaloyan; Heusch, Gerd; Tsimikas, Sotirios; Fernández-Hernando, Carlos; Berry, Sarah E.; Hall, Wendy L.; et al.
Abstract : Rationale: PCSK9 (proprotein convertase subtilisin/kexin type 9) circulates in a free and lipoprotein-bound form, yet the functional consequence of the association between PCSK9 and HDL (high-density lipoprotein) remains unexplored. Objective: This study sought to interrogate the novel relationship between PCSK9 and HDL in humans. Methods and Results: Comparing lipoprotein and apolipoprotein profiles by nuclear magnetic resonance spectroscopy and targeted mass spectrometry measurements with PCSK9 levels in the community-based Bruneck study (n=656) revealed a positive association of plasma PCSK9 with small HDL, alongside a highly significant positive correlation between plasma levels of PCSK9 and apolipoprotein C3 (apoC3), an inhibitor of lipoprotein lipase. The latter association was replicated in an independent cohort, the SAPHIR study (Salzburg Atherosclerosis Prevention Program in Subjects at High Individual Risk; n=270). Thus, PCSK9-HDL association was determined during the postprandial response in two dietary studies (n=20 participants each, 8 time points). Peak triglyceride levels coincided with an attenuation of the PCSK9-HDL association, a loss of apoC3 from HDL, and lower levels of small HDL as measured by nuclear magnetic resonance spectroscopy. Crosslinking mass spectrometry upon isolated HDL identified PCSK9 as a potential HDL-binding partner. PCSK9 association with HDL was confirmed through size-exclusion chromatography and immuno-isolation. Quantitative proteomics upon HDL isolated from patients with coronary artery disease (n=172) returned PCSK9 as a core member of the HDL proteome. Combined interrogation of the HDL proteome and lipidome revealed a distinct cluster of PCSK9, phospholipid transfer protein, clusterin, and apolipoprotein E within the HDL proteome that was altered by sex and positively correlated with sphingomyelin content. Mechanistically, HDL facilitated PCSK9-mediated low-density lipoprotein receptor degradation and reduced low-density lipoprotein uptake through the modulation of PCSK9 internalization and multimerization. Conclusions: This study reports HDL as a binder of PCSK9 and regulator of its function. The combination of -omic technologies revealed postprandial lipemia as a driver of PCSK9 and apoC3 release from HDL. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03191513; URL: https://www.isrctn.com ; Unique identifier: ISRCTN20774126. Abstract : Supplemental Digital Content is available in the text.